ANALISIS KINERJA PEGAWAI DALAM PROGRAM PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENKAP (PTSL) DI KANTOR PERTANAHAN KABUPATEN TAKALAR - Nurhikmah, Nurhikmah; Mappamiring, Mappamiring; Wahid, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aimed to find out how the performance of employees in the complete systematic land registration acceleration program (PTSL) at the land office of Takalar Regency. This study used descriptive qualitative research. The number of informants in this study were 7 (seven) people. Data collection techniques used interviews, observation, documentation, literature study, company/office documents, and media analysis. The results showed that the analysis of employee performance in the complete systematic land registration acceleration program (PTSL) at the Takalar Regency land office had run effectively. In the aspect of leadership, it had been effective in giving instructions to improve employee performance. From the aspect of competence/ability, it run effectively because of the employee's thoroughness and mastery of his work. From the aspect of motivation, it was quite good because there was a reward system that encouraged employee morale. After doing research, It found new things including cooperation and work discipline that run effectively because of community satisfaction with employee performance in the services provided by the Takalar Regency land office employee. Keywords: Employee Performance, Complete Systematic Land Registration Program